2018
DOI: 10.1016/j.jcp.2018.07.033
|View full text |Cite
|
Sign up to set email alerts
|

A pressure-corrected Immersed Boundary Method for the numerical simulation of compressible flows

Abstract: The development of an improved new IBM method is proposed in the present article. This method roots in efficient proposals developed for the simulation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…More details about the algorithmic structure of rhoCentralFoam solver can be found in Ref. [13]. In our recent work [15], this solver has been combined with a diffused-interface IBM to simulate viscous compressible flows.…”
Section: Basic Solver In Openfoammentioning
confidence: 99%
See 2 more Smart Citations
“…More details about the algorithmic structure of rhoCentralFoam solver can be found in Ref. [13]. In our recent work [15], this solver has been combined with a diffused-interface IBM to simulate viscous compressible flows.…”
Section: Basic Solver In Openfoammentioning
confidence: 99%
“…The diffused-interface IBM can be regarded as a continuous forcing approach. The boundary is smeared by distributing a forcing term [10,12] and a source term [13] to the surrounding Cartesian grid points via a delta function [14]. After that, these two terms are added to the momentum equation and energy equation, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of fluid flow around the thin object, the solution may present a situation in which simulated vibrations occur within the calculated pressure (Bailoor, Annangi, Seo, & Bhardwaj, 2017;Boukharfane, Eugênio Ribeiro, Bouali, & Mura, 2018;Horng, Hsieh, Yang, & You, 2018). These vibrations are occasionally considered IBM features; however, such effects can be eliminated or drastically reduced by applying a second-stage correction to the calculated pressure (Frantzis & Grigoriadis, 2019;Griffith & Luo, 2017;Lee & LeVeque, 2003;Riahi, Meldi, Favier, Serre, & Goncalves, 2018;Sotiropoulos & Yang, 2014;Ya, Takeuchi, & Kajishima, 2007). This technique is a relevant improvement, particularly for the FSI numerical simulations of thick structures (such as shells) and other thin interfaces that pose a major challenge to generating FSI solutions with IBM (Wang, Yan, & Tian, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the IBM was extended into compressible flow simulations by Ghias et al In addition, Takahashi et al and Luo et al proposed the simplified IBM for compressible viscous flow based on the IBM by Mittal et al Furthermore, the immersed boundary‐lattice Boltzmann method (IB‐LBM) was proposed by Feng and Michaelides . Recent works related to the IBM are mostly confirmed in the applications, such as fluid‐motion coupled simulation of a falling plate by Lau et al and fluid‐structure coupled analysis of an elastic object in a compressible flow by Kim et al Furthermore, progressive achievements related to the IBM are confirmed in studies of turbulent simulation with LBM by Xu et al, application to aeroacoustics problem by Schlanderer et al, and implementation to OpenFOAM by Riahi et al…”
Section: Introductionmentioning
confidence: 99%